RELATIONSHIP BETWEEN TEACHER'S PEDAGOGICAL COMPETENCY AND STUDENT'S ATTITUDES TOWARDS HOME ECONOMICS EDUCATION - Ugwu, Benedet (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Home economics is an essential component of the educational ecosystem, reflecting the vital skills that could help students navigate and thrive in today's world. There are insinuations suggesting an insufficient enrollment in the Nigerian educational context. Past studies have underscored the potential reasons for declining home economics enrollment. However, little is known about the influence of a teacher's pedagogical expertise. The current study examined the correlation between teachers' pedagogical competence and student attitudes towards home economics. Eighty-seven students enrolled in home economics courses at two public tertiary institutions in Enugu state completed a self-report measure of teachers' pedagogical competence and attitudes towards home economics. A Pearson's product-moment correlation analysis was computed on the data. The result showed linear and normally distributed variables as observed in the Shapiro-Wilk's test (p > .05). Thus, there was a statistically significant, positive correlation between TPC and ATHE, r (85) = .41, p < .001. Notably, the result indicated that TPC explained about 2.16% of the variation in students' attitudes towards home economics. The result has implications for developing and sustaining home economics in Nigeria's educational system.